Kajian Tafsir Lisan tentang non-Muslim Perspektif Kiai Haji Maimun Zubair - Nova Saha Fasadena; Wardatul Jannah (Al-Manar: Jurnal Kajian Alquran dan Hadis, 2022)
On social media, there is a lot of hate speech and discriminatory behavior against non-Muslims carried out by radical Islamic groups. Even though it is contrary to what was taught by the Prophet and Ulama such as Walisongo. This if left unchecked will have an impact on disharmony and the development of intolerant behavior. This study examines the oral interpretations of scholars who have a depth of knowledge and are recognized for their wisdom by other scholars, especially Kiai Haji Maimun Zubair. A great Ulama caregiver PP. Al-Anwar Rembang regularly held an interpretation recitation during his lifetime with his students and the general public. The method used is to watch, listen and take notes, meaning that the researcher watches the video interpretation of Kiai Haji Maimun Zubair on YouTube which is uploaded by the official account of the pesantren (PP al-Anwar), then the researcher listens to what is conveyed and notes several important points for further study. deeper through discourse analysis. The results of the research on the oral interpretation of Kiai Haji Maimun Zubair in QS. Al-Isra: 53 on youtube shows that: 1) To communicate with nonMuslims, the best step is not to offend him as an expert in hell or make fun of his Lord. 2) believe that the concept of religious people is good, meaning that religious people are obedient to their religion which has five basic legal rules for marriage, cannot recognize property rights, cannot kill, cannot damage reason, can not damage other people's honor.